Three Phase Motor Centrifugal Machines Speed Control Using Pid Fuzzy Method - Trio Yus Peristiaferi; Rusdhianto Effendie; Josaphat Pramudijanto (Jurnal Teknik ITS, 2015)
Induction motor speed settings are still done manually by changing the position of the shaft or the size of the puli engine centrifugal. This method resulted in an arrangement with the speed of the motor will be difficult to control as expected. Inappropriate speed settings can also lead  to  less  sugar  production  results.  It  is  therefore  necessary  to maintain the control method of motor speed when load is added while experiencing the process of starting, spinning and breaking. The controller that is used is the PID Fuzzy. In a using simulation and implementation of  using  controller PID Fuzzy  having  the  averages  error  when  processing starting, spinning and breaking a dising about 0.51 % and about 1.06 %. So this final project hoped can help increase the efficiency of the centrifugal on sugar factory machine.